Step 1: Find one term from both equations on the left side of the equality sign that, when added together, equal 0 (thus canceling each other out.) The two terms that fit this description is -y and y. Add them together we get 0.
Step 2: Add the remaining like terms from both equations.
3x + x = 4x
-5 + 1 = -4
4x = -4
Step 3: Divide both sides by 4 to isolate the variable x.
4/4x = -4/4
x = -1
Step 4: We have x, now we need to find y. Take an original equation (either one is fine) and substitute -1 for x.
3(-1)⇒ -3 + y = 1
Step 5: Isolate 'y' by doing inverse operations to both sides of the equation.
-3 + 3 + y = 1 + 3 ⇒ y = 4
Answer: (-1,4)